Tripathi, Amarendu “Kautilya’s Arthshastra and Its Contemporary Relevance in Indian International Relations” - Tripathi, Amarendu (जम्बूद्वीप - the e-Journal of Indic Studies (ISSN: 2583-6331), 2024)
This paper explores the enduring relevance of Kautilya's Arthshastra in the context of contemporary Indian international relations. With a rich historical background and a comprehensive framework for statecraft, diplomacy, and strategy, Kautilya's treatise continues to provide valuable insights into India's foreign policy decisions and actions on the global stage. Drawing upon an extensive literature review and an in-depth analysis of the Arthshastra, this research examines how Kautilya's ideas intersect with modern international relations theories, such as realism and power politics. Through case studies and real-world examples, this paper demonstrates the practical application of Kautilya principles in understanding and shaping India's international relations. While acknowledging critiques and challenges, this study underscores the enduring relevance of Kautilya's Arthshastra as a foundational text for comprehending India's role in the complex web of international politics. By bridging the ancient wisdom of Kautilya with contemporary foreign policy challenges, this research contributes to a nuanced understanding of India's diplomatic strategies and its evolving position in the global arena.